Comparative analysis of digital mammography and contrast-enhanced mammography in diagnosing suspicious breast calcifications: implications for surgical decision-making - Marwa Mohamed Taher Mohamed ElSayad; Maha Hussein Mohamed Helal; Omar Hussein Omar; Ahmed Gamal Eldeen Othman; Marwa Elsayed Abdelrahman Ibrahim (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Breast calcifications can be an indicator of early-stage breast cancer. While Digital Mammography (DM) remains the gold standard for detecting breast microcalcifications, its ability to differentiate between benign and malignant types based solely on morphology and distribution is limited. Contrast-Enhanced Mammography (CEM) incorporates pathological contrast-enhancement, leading to a more confident diagnosis, and offering a faster and more cost-effective tool than breast magnetic resonance imaging. CEM allows for a single scan assessing both microcalcification morphology using low energy images and lesion vascularity using high energy subtracted images. Purpose This study aimed to compare the diagnostic accuracy of CEM and DM in evaluating suspicious breast calcifications, with a focus on characterizing breast masses (benign vs. malignant), delineating tumor extent, and assessing the clinical impact of these imaging modalities on surgical decision-making. Results Out of the 54 identified breast lesions, 19/54, (35%) were benign and 35/54, (65%) were malignant. Calculated sensitivity, specificity, positive and negative predictive values and total accuracy of DM were 91.4%, 70.8%, 62.7%, 93.9%, and 78% respectively as compared to 85.7%, 90.7%, 83.3%, 92.2%, and 89% for CEM. Regarding size estimation, Results showed that size of tumor by CEM was more correlated to that by pathology, correlation coefficient (r = 0.86), than DM and pathology,(r = 0.588). Mean difference in diameter (compared to pathology) for CEM was 1.28 mm, and 2.8 mm for DM, with no effects on surgical decision-making. Cronbach’s Alpha as a measure of reliability was 0.740 between size measurement by DM and pathology, indicating acceptable reliability. However, it was 0.92 between CEM and pathology, indicating excellent reliability. Conclusions CEM exhibits higher specificity than DM in assessing suspicious breast microcalcifications. CEM provided tumor size measurements that correlated more with pathological findings compared to DM. While these measurement discrepancies were minor and did not affect surgical planning, CEM proved impactful in when multicentricity was identified by CEM but overlooked in initial DM evaluations. This was evident in patients with dense breasts or instances of satisfaction of search error, where subtle lesions indicative of multicentricity were initially missed, highlighting CEM’s potential to enhance surgical decision-making in such scenarios.